A Critical Reflection on African Maritime Cybersecurity Frameworks - Hailu Sime, Tefesehet (Scientia Militaria - South African Journal of Military Studies, 2023)
With a coastline of 26,000 nautical miles and 38 out of 55 African states being either coastal or island states, trading activities on the continent are facilitated by over a hundred port facilities in the region, which make up 90 per cent of African seaborne trade. These factors indicate that the continent is dependent on well-run ports, effective protection of its maritime resources, and regulated shipping. Regulating the maritime sector requires new technologies that come at the cost of cyber vulnerabilities. However, in Africa, there are very few legal instruments, both at national and at regional level, specifically addressing the issue of cyberattacks on ships and port facilities.Given the lack of attention given to maritime security and the lack of collective action from African states, the study on which this article reports, sought to provide a critical reflection on how cyber technology is affecting is affecting the African maritime domain; and the consequences that could manifest should the cybersecurity of ships, ports, and their critical infrastructure continue to be ignored. The aim of this study was to broaden the understanding of the maritime cybersecurity legal frameworks in Africa by using the ‘black letter’ methodology, which is a positivist approach described by academics as being the best avenue by which to assess the existence, meaning and application of a defined system of legal principles. In engaging with those conventions, policies, laws, and regulations that are currently guiding the area of maritime cybersecurity, the study sought to identify the gaps in the legal frameworks on the continent and to provide policy recommendations.